The pains of police custody for children: a recipe for injustice and exclusion? - Bevan, Miranda (2021)
This article utilizes the sociology of punishment, particularly the work of Gresham Sykes in 1958, to develop an understanding of the particular pains of police custody for children, drawing on the first comprehensive study in England and Wales to review the police custody process as a whole from the perspective of the child suspect. By identifying the correspondences and contrasts between the experience of adult sentenced prisoners and child suspects in detention, the analysis illuminates the damaging ramifications of harsh custody processes for children, both in terms of their effective participation in the justice process and their ongoing attitudes towards the police